PENGGUNAAN DEDAK GANDUM KASAR (WHEAT BRAN) SEBAGAI PENGGANTI JAGUNG DENGAN KOMBINASI TEPUNG DAUN MENGKUDU (Morinda citrifolia) UNTUK MENGHASILKAN TELUR PUYUH SEHAT RENDAH KOLESTEROL DAN KAYA VITAMIN A - Ruri Anggun Nastiti; Widya Hermana; Rita Mutia (Buletin Ilmu Makanan Ternak, 2014)
(SUBTITUTION CORN WITH WHEAT BRAN COMBINATED Morinda citrifolia LEAVES TO PRODUCE HEALTHY QUAIL EGGS LOW CHOLESTEROL AND RICH IN VITAMIN A)Egg is source of protein food that has consumed by people. People choose it because the price relatively cheap and the content of nutrients was completed. However, some people restrict to consume it because cholesterol on egg yolks is high. Quail eggs has cholesterol content higher than hens eggs every gram of weight. The study was done to analyze the quality of eggs , cholesterol levels and vitamin A on eggs. The experimental design used in this research was completely randomized design (CRD) for quality of egg with 4 treatments and 4 replication. R0 control, R1(6% Morinda citrifolia leaf meal and 5% wheat bran), R2(6% Morinda citrifolia leaf meal and 10% wheat bran) and R3(6% Morinda citrifolia leaf meal and 15% wheat bran). R1, R2, and R3 have good result in quality of eggs. R0 have the lowest cholesterol and the highest vitamin A in R2. Keywords: cholesterol, Morinda citrifolia leaves, quail egg, vitamin A, wheat bran